Apollo 13 [videorecording (Blu-Ray)] - Hanks, Tom; Paxton, Bill; Harris, Ed, 1950-; Bacon, Kevin, 1958-; Sinise, Gary; Quinlan, Kathleen, 1954- (Universal Studios Home Entertainment, 2015)
A big-picture reenactment of the 1970 Apollo lunar mission that ran into problems. Stranded 205,000 miles from the Earth in a crippled spacecraft, astronauts Jim Lovell, Fred Haise and Jack Swigert fight a desperate battle to survive.